A systematic review of context-aware technology use in foreign language learning. Issue 3 (4th March 2022) - Lee, Sangmin-Michelle
Abstract: As context plays a critical role in foreign language (FL) learning, context-aware technology is a promising tool for supporting FL learning. The present study examined studies published between 2000 and 2018 to understand the trends of technology and related research and the current issues with context-aware technology in FL learning. This review included 75 empirical studies and 13 system-descriptive studies. The empirical studies were further examined in terms of publication year, methodology, participants, languages, device types, and the effectiveness of the technology based on FL learning results. Most of the studies indicated positive effects of the technology in the affective, linguistic, socio-cultural, and cognitive domains. The review also found issues with the reviewed studies, including the research methods, research sustainability, and practicability of the technology. The review results showed that the number of publications per year fluctuated rather than increased over the studied period. Students' perceptions of the use of context-aware technology in FL were the most common focus of the reviewed research; far fewer empirical studies were found that assessed students' actual language learning outcomes. The results of this study suggest that more long-term, pedagogy-informed empirical studies based on students' actual learning outcomes are required to verify the effectiveness of context-aware technology on FL learning and to help effectively integrate such technology into learning in the future.